The aged rhesus macaque manifests Braak stage III/IV Alzheimer’s-like pathology - Paspalas, Constantinos D. (Alzheimers Dement, 2017)
INTRODUCTION: An animal model of late-onset Alzheimer’s disease is needed to research what causes degeneration in the absence of dominant genetic insults and why the association cortex is particularly vulnerable to degeneration. METHODS: We studied the progression of tau and amyloid cortical pathology in the aging rhesus macaque using immunoelectron microscopy and biochemical assays. RESULTS: Aging macaques exhibited the same qualitative pattern and sequence of tau and amyloid cortical pathology as humans, reaching Braak stage III/IV. Pathology began in the young-adult entorhinal cortex with protein kinase A-phosphorylation of tau, progressing to fibrillation with paired helical filaments and mature tangles in oldest animals. Tau pathology in the dorsolateral prefrontal cortex paralleled but lagged behind the entorhinal cortex, not afflicting the primary visual cortex. DISCUSSION: The aging rhesus macaque provides the long-sought animal model for exploring the etiology of late-onset Alzheimer’s disease and for testing preventive strategies.